Does implementing a regime of dexamethasone before planned cesarean section at term reduce admission with respiratory morbidity to neonatal intensive care unit? A randomized controlled trial. (4th March 2018) - Nooh, Ahmed Mohamed; Abdeldayem, Hussein Mohammed; Arafa, Eisa; Shazly, Sherin Attia; Elsayed, Hany; Mokhtar, Wesam A.
Abstract: Aim: To assess the effectiveness of dexamethasone before planned cesarean section (CS) at term in reducing admission with respiratory morbidity to neonatal intensive care units (NICU). Methods: A prospective randomized controlled trial which was conducted at an Egyptian teaching hospital. Participants at ≥38 weeks gestation who were planned to have planned CS were recruited. They were randomized into a treatment group (636 women) who received three intramuscular (IM) doses of dexamethasone 8 mg, 8 h apart, and control group (636 women) who have not received dexamethasone, before having planned CS. The primary outcome was admission to NICU with respiratory morbidity, which was analyzed by intention to treat. Results: A total of 1272 planned CS's were carried out in this trial. They were associated with less admission to NICU with respiratory morbidity in women treated with dexamethasone than in women not treated (13 (2.0%) versus 21 (3.3%), respectively). However, the difference between the two groups failed to show a statistical significance ( p = .88). Conclusion: Dexamethasone administration before planned CS at term, as compared to routine management without antenatal steroids, was not associated with a statistically significant reduction in the incidence of admission to NICU with respiratory morbidity.